Guano and the opening of the Pacific world : a global ecological history - Cushman, Gregory T., 1971-; Cambridge eBooks (Cambridge : Cambridge University Press, 2013)
For centuries, bird guano has played a pivotal role in the agricultural and economic development of Latin America, East Asia and Oceania. As their populations ballooned during the Industrial Revolution, North American and European powers came to depend on this unique resource as well, helping them meet their ever-increasing farming needs. This book explores how the production and commodification of guano has shaped the modern Pacific Basin and the world's relationship to the region. Marrying traditional methods of historical analysis with a broad interdisciplinary approach, Gregory T. Cushman casts this once little-known commodity as an engine of Western industrialization, offering new insight into uniquely modern developments such as environmental consciousness and conservation movements; the ascendance of science, technology and expertise; international relations; and world war.
Prologue -- The Guano Age -- Neo-Ecological Imperialism -- Where Is Banaba? -- Conservation and the Technocratic Ideal -- The Most Valuable Birds in the World -- When the Japanese Came to Dinner -- The Road to Survival -- Guano & the Blue Revolution.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Guano -- Peru -- History; Guano industry -- Pacific Area -- History; Guano -- Social aspects -- History; Guano -- Environmental aspects -- History; Phosphate industry -- History; Human ecology -- History; Peru -- Environmental conditions; Pacific Area -- Commerce -- History; Pacific Area -- Environmental conditions; Electronic books